Transformasi Digital Badan Pusat Statistik Indonesia Pada Era Big Data - Revina Siregar (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In the 20th century, the development of technology is increasingly rapid. Digital transformation and big data are the impact of technological developments that occur continuously. The purpose of this paper is to explain the implementation of digital transformation at the Central Bureau of Statistics as well as the opportunities and challenges faced. Through a literature review on the digital transformation of the Central Bureau of Statistics in the era of big data, it is found that the Indonesian Central Bureau of Statistics has implemented digital transformation in its business processes such as online surveys, centralized data management systems, dissemination through social media, Integrated Statistical Services (PST), and SILASTIK. In addition, digital transformation also has various opportunities such as facilitating the business activities of Statistics Indonesia in the collection to dissemination process, as well as challenges such as data security and privacy. Thus, digital transformation plays an important role for Statistics Indonesia in improving the quality of statistics, optimizing the use of big data technology, and adjusting to changes so that the data produced remains relevant.